HUBUNGAN EFEKTIVITAS METODE PEMBERIAN TUGAS (RESITASI) DENGAN HASIL EVALUASI BELAJAR MAHASISWA PADA MATA KULIAH KESEHATAN REPRODUKSI DAN ASUHAN KEBIDANAN I DI STIKES PAYUNG NEGERI PEKANBARU - Dona Martilova, Husna Farianti Amran, (Jurnal Martenity and Neonatal, 2015)
The method of assignment is a way of teaching and learning which gives faculty and students are doing a particular task. Then the task is accountable to the lecturer. In this way, it is expected that students learn independently, but responsible and experienced students will know the difficulties and then will try to overcome these difficulties, so this method is the center of activity in students. This study aims for know there a relationship between the effectiveness of the method of administration tasks with the results of the evaluation of student learning in the subject of Reproductive Health and Midwifery Care I in STIKes Payung Negeri Pekanbaru.Metode Analytical study is cross-sectional approach. Using primary data through questionnaires and secondary data from Study Result Card (KHS)Objective : To identify is the correlation between giving assignment method effectivity with the evaluation result of study at subject reproductive health and midwifery care 1st in STIKes Payung Negeri Pekanbaru .Method : The study type was analytical with cross-sectional approach. Primary data was collected from questionnaire and the secondary data from Study Result Card. The Population in this study all of midwifery student (310 person) with the sample all of midwifery student 3rd semester (110 person). The data analyzed with Spearman rank test correlation and represented in distribution frequency table.Result : Study show giving assignment method is an effective category at subject Reproductive Health 55,36%, and Midwifery Care 1st 52,68%. Evaluation result of study is good category at subject Reproductive Health 51,79%, and Midwifery Care 1st 41,96%. Based on the coefficient correlation of Rank Spearman there were that significant correlation at subject Reproductive Health (r = 0,405) and Midwifery Care 1st( r = 0,609). Conclusion : There are significant correlation between giving assignment method effectivity with the evaluation result of study at subject reproductive health and midwifery care 1st